ChemInform Abstract: 1, 4‐Naphthoquinones in H‐Bond‐Directed Trienamine‐Mediated Strategies. Issue 46 (24th October 2013) - Albrecht, Lukasz; Villegas Gomez, Clarisa; Jacobsen, Christian Borch; Joergensen, Karl Anker
Abstract Based on a trienamine‐mediated H‐bond directed [4 + 2] cycloaddition of 2, 4‐dienals and 1, 4‐naphthoquinones a stereoselective approach to enantioenriched carboannulated naphthoquinones and dihydronaphthoquinones is developed.